Effect of BAP (6-Benzyl Aminopurine) on In Vitro Shoot Growth of Curcumas - Rustikawati Rustikawati; Catur Herison; Entang Inoriah; Vera Dwisari (AGRITROPICA : Journal of Agricultural Sciences, 2021)
Curcuma sp has been widely investigated for its anti-cancer properties. Conventionally, vegetative propagation needs a long time to produce a large number of planting materials, so that it is necessary to find an alternative approach through in vitro propagation.  The effect of BAP on the in vitro shoot formation of ‘temu putih’ and ‘temu putih’ has been investigated in this study. The experiment was a 4x2 factorial with 5 replications arranged in a completely randomized design.  The first factor was the concentration of BAP i.e. 0, 1.5, 3, and 4.5 ppm.  The second factor was the curcuma species consisting of ‘temu putih’ (Curcuma zedoaria Roch.) and ‘temu mangga’ (Curcuma mangga Val.).  Each experimental unit consisted of 2 in vitro bottles, each of which planted with 1 explant bud.  Analysis of variance was conducted on percentage of live explants, shoot height, number of roots, root length, wet weight, percentage of explants that sprouted, percentage of rooted explants and shoot color.  Mean comparison was performed by the Least Significant Difference (LSD).  The results showed that there was no interaction between BAP concentration and genotype on any variable observed.  The shoot growth of ‘temu putih’ was significantly higher than ‘temu mangga’ in vitro.  The best concentration of BAP for the growth of ‘temu putih’ and ‘temu mangga’ shoots was 1.5 ppm.